Bis(formylpyrrolyl) cobalt complexes as mediators in the reversible-deactivation radical polymerization of styrene and methyl methacrylate. (21st March 2018) - Cruz, Tiago F. C.; Machado, Pedro M. M.; Gomes, Clara S. B.; Ascenso, José R.; Lemos, M. Amélia N. D. A.; Bordado, João C.; Gomes, Pedro T.
Abstract : Bis(formylpyrrolyl) cobalt complexes mediate the reversible-deactivation radical polymerization of styrene and methyl methacrylate. Abstract : The combination of [Co (II) {κ 2 N, O-NC4 H3 -C(H)O}2 (PMe3 )2 ] (1 ) and tert -butyl-α-bromoisobutyrate ( t BiB-Br) is a suitable initiation system for controlling the radical polymerization of styrene, by an atom transfer radical polymerization (ATRP) mechanism, below 70 °C and of methyl methacrylate, by an organometallic mediated radical polymerization (OMRP)/catalytic chain transfer (CCT) interplay mechanism, below 50 °C. The pure ATRP nature of styrene polymerization allowed the synthesis of the polystyrene- b -poly(methyl methacrylate) block copolymer, as confirmed by GPC/SEC and DOSY NMR studies. Attempts to isolate a Co(iii ) species containing a Br atom (Co(iii )–Br ), supposedly a key ATRP deactivator, by reacting1 and t BiB-Br quantitatively afforded the cationic Co(iii ) complex [Co (III) {κ 2 N, O-NC4 H3 -C(H)O}2 (PMe3 )2 ]Br (2 ). Metathetic exchange reactions of complex2 with TlX gave rise to analogues of the type [Co (III) {κ 2 N, O-NC4 H3 -C(H)O}2 (PMe3 )2 ]X (3a, X = BF4 − ;3b, X = BPh4 − ), containing non-coordinating anions. In the absence of a radical initiator, complex2 mediated the formation of polystyrene and poly(methyl methacrylate), with poor control, likely via a generation of activators by a monomer addition (GAMA) mechanism. Complexes3a and3b, however, have been shown to be completely inactive. Addition of 0.5 equivalents of AIBN to2 drastically improved the molecular weight control in the polymerization of styrene, at 70 °C, through a reverse-ATRP mechanism.